2021
DOI: 10.1159/000514640
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Reality with HoloLens® in Parotid Tumor Surgery: A Prospective Feasibility Study

Abstract: <b><i>Introduction:</i></b> Augmented reality can improve planning and execution of surgical procedures. Head-mounted devices such as the HoloLens® (Microsoft, Redmond, WA, USA) are particularly suitable to achieve these aims because they are controlled by hand gestures and enable contactless handling in a sterile environment. <b><i>Objectives:</i></b> So far, these systems have not yet found their way into the operating room for surgery of the parotid gland. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…In otolaryngology and maxillofacial surgery, studies have demonstrated improved understanding of tumor-related anatomy and planning of surgical approach when MR was used instead of conventional radiological imaging [ 8 , 9 ]. Mitani et al [ 8 ] found that MR facilitated recognition of dissection lines in parotid tumor surgery, where consideration of detailed maxillary anatomy is of critical importance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In otolaryngology and maxillofacial surgery, studies have demonstrated improved understanding of tumor-related anatomy and planning of surgical approach when MR was used instead of conventional radiological imaging [ 8 , 9 ]. Mitani et al [ 8 ] found that MR facilitated recognition of dissection lines in parotid tumor surgery, where consideration of detailed maxillary anatomy is of critical importance.…”
Section: Resultsmentioning
confidence: 99%
“…In otolaryngology and maxillofacial surgery, evidence suggests that MR enables easier extracapsular dissection of parotid tumors, which is related to lower complication rates, improved preservation of glandular tissue, and decreased incidence of saliva fistulas [ 9 ]. Tian et al [ 35 ] reported satisfactory use of intraoperative MR in cochlear implant surgery due to improved positioning of the implant.…”
Section: Resultsmentioning
confidence: 99%
“…Manual registration, which showed a mean error of alignment of 12.4 mm, would be another option. After appropriate training or assistance by fiducial markers, the error was reduced to 10 mm [ 11 , 33 ]. Consequently, image-based registration with Vuforia, which is much more accurate, is still the method of choice for most applications [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Examples of applications in the operating theater are orthognathic surgery, oncology including parotid surgery, and traumatology. Anatomical and pathological structures, drilling and implant position, resection margins, and reconstructive planning are visualized using different AR technologies [ 10 , 11 ]. Similar examples can also be found on cadavers [ 12 - 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…General-purpose OST-HMDs, such as the Microsoft© HoloLens ™ 1 and 2 and Magic Leap ™ 1 devices, are increasingly proposed as promising tools in the context of computer-aided surgery. Their use has been demonstrated on phantoms [12][13][14][15], in cadaver studies [16,17], and/or in pre and intra-operative planning tasks [18][19][20][21][22]. More recently, one study demonstrated the use of Microsoft© HoloLens ™ 2 device in spine surgery on a real patient [23].…”
Section: Introductionmentioning
confidence: 99%